Avoidance coping mediates the effect of hardiness on mental distress symptoms for both male and female subjects. Issue 1 (22nd October 2021) - Thomassen, Ådne G.; Johnsen, Bjørn Helge; Hystad, Sigurd W.; Johnsen, Grethe E.
Abstract : The personality disposition hardiness has been shown to be associated with adaptive coping strategies and is considered an important protective factor against development of mental health symptoms. One of the criticisms found in the hardiness literature concerns the question whether the construct is equally important for men and women. Using a prospective design in a moderated mediation model, regression analyses were performed to examine the effect of avoidance coping in the association between hardiness and mental distress. The effect of biological sex was examined in the association between hardiness and avoidance coping. Our sample included 410 civilian personnel employed in a military organization. The results showed that higher hardiness levels were associated with lower reported use of avoidance coping, which in turn was associated with lower levels of distress symptoms. Avoidance coping mediated the effect of hardiness on anxiety symptoms and this indirect effect was not moderated by biological sex. These results indicate that hardiness operates similarly for women and men as a factor influencing mental distress symptoms.